Kajian Etnobotani, Fitokimia Dan Bioaktifitas Tumbuhan Obat Kabupaten Sukoharjo, Jawa Tengah - Аrbаin, Dаyаr; Pangestu, Hadi (CV RIFAINSTITUT, 2022)
The people of District Sukoharjo in the Midle Java Province have traditionally use medicinal plants for maintaining their health and to cure their illness by using what so called Jamu Gendong. The verification, validation and standardization of these medicinal plants in general, as yet, are not satisfactory. In order to obtain the better understanding of this Jamu Gendong, the Study of Ethnobotany, Phytochemistry, and Bioactivity of Sukoharjo District has been carried out in 3 Sub-Districts in March 2021 started with an interview with 9 randomly selected traditional heales then continued by literature review, to find correlatioin between traditional use, chemical constiuents and bioaktivities of those medicinal. 12 medicinal plants samples with the the highest Use Value (UV) 1 owned by Ginger (Zingiber officinale) and Galangal (Alpinia galanga), the highest Relative Frequency of Citation (RFC) Value 1 was owned by Kencur (Kaempferia galanga) and (Zingiber officinale) b and the highest Relative Importance (RI) 0.75 belonged to White Turmeric (Boesenbergia rotunda) and Lengkuas (Alpinia galanga) were obtained. In general it can be concluded that most of medicinal plants used by people from the Sukoharjo District contained chemical consttiuents and bioactivities closely related to their traditional use. It is hoped that this work can be continued for more detailed work related to dosage, validatioan of the the usage, and state the standar of safety in order to obtain what is called verification, validation and standtrdization of traditional medicines